Diagnostic Accuracy, Prescription Behavior, and Watchful Waiting Efficacy for Pediatric Acute Otitis Media. (January 2019) - Brinker, David L.; MacGeorge, Erina L.; Hackman, Nicole
Current guidelines recommend "watchful waiting" (WW) as an alternative to immediate antibiotic treatment. Continued high rates of antibiotic use suggest that WW may be underutilized. We conducted a retrospective chart review of 474 pediatric acute otitis media (AOM) cases at a clinic in central Pennsylvania. We assessed physical examination findings, diagnostic behavior, WW utilization, prescription writing, and filling in cases of pediatric AOM to evaluate the underutilization of WW. We evaluate diagnostic consistency with published guidelines and rates of antibiotic prescription resulting from misdiagnosis. We report WW instructions and compliance, and prescription filling behaviors. Fifty percent of AOM diagnoses in this sample were not supported by physical examination findings. The majority of these AOM diagnoses received antibiotic prescriptions, suggesting that unsupported diagnoses translated to injudicious prescribing. WW instructions corresponded to 57% fewer filled prescriptions and longer fill delay. We discuss the implications and recommendations to improve antibiotic stewardship.